الكتابات الغربية والعلاقة بالعدمية والدين: ما الذي ينبغي أن ندركه؟: Western Literature and the Relationship to Nihilism and Religion: What should we Recognize? - Abdel Qadir Mirzaq - مرزاق, عبد القادر (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2018)
تسعى هذه الدراسة إلى البرهنة عن وجود وجه سلبي خفي في الكتابات الغربية، يضمر القول بغياب القيم، والعدمية، وإعلان موت الإله في آخر المطاف، وهو وجه يغيب عنا كثيراً في تناولنا العربي، وفي الوقت نفسه وجود وجه آخر إيجابي، خفيٌّ عنا أيضاً، يدعو إلى العودة إلى أحضان القيم، والدين، والصلة بالله. وهذه ثنائية يتأرجح فيها الفكر الغربي منذ قدمه، في كل أنواع الكتابة، حاولت الكشف عنها من خلال نصوص أصحابها الغربيين أنفسهم. This study seeks to demonstrate the existence of a hidden negative feature in the Western writings, often Arabic writings do not reveal. This feature has to do with the absence of values, nihilism, and ultimately “declaration” of the death of God. At the same time there is another positive feature in Western thought, hidden from us as well, calling for a return to the embrace of values, religion, and the link to God. Western thought has been swinging in this duality in all types of its writing ever since its inception. The study tries to reveal this phenomenon through texts of Western writhers themselves.